2021
DOI: 10.1027/1866-5888/a000261
|View full text |Cite
|
Sign up to set email alerts
|

How Communication in Organizations Is Related to Foci of Commitment and Turnover Intentions

Abstract: Abstract. The current study analyzes how two components of perceived organizational communication (vertical and horizontal) are related to employee turnover intentions via three types of affective commitment foci (organization, supervisor, and team). Using second-order confirmatory factor analysis and structural equation modeling techniques with a large cross-sectional dataset ( n = 3,317), our results show that, in line with social cohesion theory, vertical communication (e.g., supportiveness from the organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Indeed, Waldman et al (2015) showed transformational leadership at the group level related to reduced turnover intentions in individuals. Related, recent work shows communication from leadership and a sense of commitment to leaders are associated with lower intentions to turnover (Holzwarth et al, 2021). Thus, we expect:…”
Section: Figurementioning
confidence: 82%
“…Indeed, Waldman et al (2015) showed transformational leadership at the group level related to reduced turnover intentions in individuals. Related, recent work shows communication from leadership and a sense of commitment to leaders are associated with lower intentions to turnover (Holzwarth et al, 2021). Thus, we expect:…”
Section: Figurementioning
confidence: 82%
“…Sociologically, disaster-affected communities actually form small communities that are united by feelings and suffering. At the timeof panicking, panic can be a cohesive factor in strengthening individual communication and ecological communication [ 42 ]. We will not find powerful mass media in small communities that are in bondage due to natural disasters [ 43 , 44 ], but what we see is cohesiveness, maintaining relationships, protecting each other, and helping each other [ 45 , 46 ], who were born from the dimension of togetherness, not because of social engineering and not political engineering, but because of natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research links strong social exchange relationships to attitudinal changes such as higher levels of job satisfaction and organizational commitment (e.g., Meyer et al, 2002), explained by well-developed affective bonds between colleagues and a more reliable, trustworthy work climate. In fact, the mere number of cooperative acts contributes to the strengthening of bonds and thus affective commitment (Holzwarth et al, 2021). Relying on reciprocity plays a significant role here because it allows individuals to engage and initiate resource exchanges between them without risking losses (Nowak, 2006), especially since individuals tend to reciprocate to those who have benefited them and punish those who engage in negative, selfish actions (Keysar et al, 2008).…”
Section: Narcissism and Organizational Citizenship Behaviormentioning
confidence: 99%